1991
DOI: 10.3354/meps075133
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and hydrological control of phytoplankton nutrient limitation in the lower Neuse River Estuary, North Carolina

Abstract: Nutrient limitation of phytoplankton production was assessed monthly from 1987 through 1990 in the lower Neuse River Estuary, North Carolina, USA, a well-mixed, mesotrophic system. Nutrient addition bioassays indicated that the lower estuary experienced a general state of nitrogen limitation, with especially pronounced limitation during summer months, a period of high phytoplankton productivity. Bioassays conducted during spring months showed significantly greater stimulation of algal productivity with the add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
111
0
2

Year Published

1995
1995
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 184 publications
(127 citation statements)
references
References 14 publications
14
111
0
2
Order By: Relevance
“…Previous nutrient addition bioassays (Paerl 1987, Rudek et al 1991, Paerl et al 1995 and nutrient uptake kinetic studies (Boyer et al 1994) have shown Nlimited conditions throughout this estuary. Parallel, independent bioassay studies conducted during this study period likewise showed N limitation (Paerl et al 1995, Pinckney et al 1997, with N enrichment achieving similar phytoplankton growth yields as N +P.…”
Section: Resultsmentioning
confidence: 99%
“…Previous nutrient addition bioassays (Paerl 1987, Rudek et al 1991, Paerl et al 1995 and nutrient uptake kinetic studies (Boyer et al 1994) have shown Nlimited conditions throughout this estuary. Parallel, independent bioassay studies conducted during this study period likewise showed N limitation (Paerl et al 1995, Pinckney et al 1997, with N enrichment achieving similar phytoplankton growth yields as N +P.…”
Section: Resultsmentioning
confidence: 99%
“…During the study period the only factor that helped to explain chlorophyll a concentrations from those tested was temperature, which is regularly found in estuaries (Eppley, 1972). However, it is relatively common for chlorophyll a to be also linked to nutrient availability (Rudek et al, 1991). One possible explanation for why chlorophyll a was not related to nitrogen or phosphorus may be that bacteria regularly outcompeted phytoplankton for available nutrients.…”
Section: Biological Responses To Discharge and Changing Doc And Nutrimentioning
confidence: 99%
“…At upstream freshwater locations, P is often the growth-limiting macronutrient (Boynton et al 1982;Larsson et al 1985). At the freshwater-saltwater transition zone, P and N may both be colimiting, while the downstream mesohaline, polyhaline zones are usually N limited Rudek et al 1991;Elmgren and Larsson 2001). The spatial and temporal overlaps of N and P limitation vary widely, and are closely controlled by hydrology, morphometry, geography, and climate.…”
Section: P Versus N Controls Of Eutrophication In the Estuarine-coastmentioning
confidence: 99%